The extraction of the glycosidal constituents of Cananga odorata Hooker filius at Thompson (Family Anonaceae) - Magat, Maria Lucia Socorro D.
The hydroalcoholic extract of ilang-ilang leaves was concentrated at reduced pressure. The concentrated extract was evaporated to dryness and the residue depigmented with acetone. The acetone extract was likewise evaporated and the residue was eluted in the column chromatography using a mixture of methanol and water as the solvent. The eluate gave an Rf value of 0.63 and its IR analysis revealed a glycoside belonging to an alcohol group.